2019
DOI: 10.22399/ijcesen.498695
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radiation Measurement in Some Soil Samples from Basra oil field, IRAQ State

Abstract: The main objective of this project is to study the natural radioactivity in the oil field environment, and its potential future effects on the workers in particular and the environment in general when increasing the concentration of natural radionuclides resulting from oil extraction. This is done by collecting a number of soil samples, were taken from one of the oil fields north of the Basra city, and the measurement was performed using a gamma ray spectrometry that contains a 3"x3" NaI(Tl) detector at gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…The specific activities of 226 Ra and 232 Th reported in previous studies [16], [17] and [18] were higher than the values of the present study. The maximum value of 40 K activity in the present study is much lower than those reported in earlier publications [10], [17], [16], [18], [19], [20], [21] and [22]. The high recorded values of the radionuclides in some soil samples are attributed to the geochemical composition and the samples were collected from the areas around the oil wells.…”
Section: Specific Activity Hazard Indicescontrasting
confidence: 81%
“…The specific activities of 226 Ra and 232 Th reported in previous studies [16], [17] and [18] were higher than the values of the present study. The maximum value of 40 K activity in the present study is much lower than those reported in earlier publications [10], [17], [16], [18], [19], [20], [21] and [22]. The high recorded values of the radionuclides in some soil samples are attributed to the geochemical composition and the samples were collected from the areas around the oil wells.…”
Section: Specific Activity Hazard Indicescontrasting
confidence: 81%
“…To nd the Skin dose contamination of the 252 Cf source using SDCC for wide energy regions. In radiation, works have been studied especially in terms of shielding and other purposes besides contamination in literature [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Using ICRP107, the 252 Cf radionuclide source is extracted and the results are provided in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Linear Attenuation Coefficient (LAC) is utilized to predict the gamma photon attenuation features through Beer-Lambert Law (BLL) [42][43][44][45][46][47][48][49][50][51][52][53]:…”
Section: 3radiation Shielding Capacitymentioning
confidence: 99%